Greenland: The Master Shaper of the Arctic? : A study about making change happen - Martinez Strömberg, Valentin Erik (Linköpings universitet, Institutionen för ekonomisk och industriell utveckling, 2019)
The Arctic region is changing. This is an oft-cited statement researcher, policy-makers and the general public say about the Arctic. But who can change the Arctic order? This academic paper is interested in determine Greenland’s role and ‘actorness’ in this changeable region. Adopting an interpretivist approach, I advocate to embrace the narrative turn in IR as a useful move to understand how Greenland, as a sub-state regional entity, can enhance its agency capacity in Arctic affairs. Using phronetical case study, govermentality and narrative analysis as main methodologies, this study decipher how the Arctic governance has changed and been shaped by different narratives and governmental practices. Greenland’s possibilities to exercise more power have been analysed through the lenses of ontological security theory because this theory is intimately related to human agency. However, this theory presents several challenges that must be overcome by doing a revision of the theory. The final results are discusses in a reflexive manner adopting four phronetical value-rational questions that policy-makers should take into account when planning any relevant strategic action, such as Greenland’s visibility and empowerment in Arctic affairs.